FORMULASI DAN EVALUASI SALEP EKSTRAK DAUN GULMA SIAM (Chromolaena odorata L.) DENGAN VARIASI BASIS SALEP - Hasrawati, A.; Famir, Yasir; Aztriana, Aztriana; Mursyid, A. Mumtihanah (Fakultas Farmasi UMI, 2019)
Siam weed leaves are one of the plants that function as wound medicine. This study aims to produce a stable ointment dosage form. Siamese weed leaf extract is formulated in the form of ointment with a variety of bases consisting of a hydrocarbon base, absorption, water soluble and emulsion. Evaluation of physical stability includes organoleptic testing, homogeneity, pH, dispersion, viscosity and flow properties carried out before and after forced conditions. Forced conditions were carried out with stock storage for 10 cycles at 50 and 350. The results of the analysis showed that the viscosity of the preparations in all formulas changed after storage at 50 and 350 for 5 days. However, the statistical results show that all formulas did not experience significant changes between before and after the stress condition treatment.